Stability: next focus in organic solar cells based on non-fullerene acceptors. (2nd March 2021) - Li, Yawen; Li, Tengfei; Lin, Yuze
Abstract : The systematic knowledge about the latest progress in the stability of non-fullerene acceptor based organic solar cells, as well as the challenges and prospects for stability improvement strategies, are reviewed. Abstract : Non-fullerene acceptors (NFAs) have been widely developed to improve the power conversion efficiencies (PCEs) of organic solar cells (OSCs). The highest PCE has reached over 18% in binary bulk heterojunction (BHJ) NFA-OSCs, approaching the threshold for commercial applications, while the most stable NFA-OSCs have been inferred with a potential lifetime of 22 years. The instability of NFA-OSCs has not been paid enough attention and becomes one of the major barriers to their commercialization. Herein, we present a systematic discussion on degradation mechanisms of NFA-OSCs, in which we focused on the fundamentals of instability in NFA-OSCs, including photo-oxidation, morphology instability, and interlayer induced instability. Meanwhile, the recent progress and promising strategies to improve the stability of NFA-OSCs are presented in the themes of their molecular design, a third component in the blend film and passivation of the interlayer. We believe that a study on their stability should be the next focus in the field of NFA-OSCs.